2016
DOI: 10.1007/978-3-319-25226-1_24
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing Redundancy Among Genes Selected Based on the Overlapping Analysis

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Abstract. For many functional genomic experiments, identifying the most characterizing genes is a main challenge. Both the prediction accuracy and interpretability of a classifier could be enhanced by performing the classification based only on a set of discriminative genes. Analyzing overlapping between gene expression of different classes is an effective crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…To evaluate Slope-Hunter’s estimations of the G 1 class membership probabilities, we calculated the mean probability for the SNPs identified as the G 1 class. Moreover, the misclassification error rate [18, 19] was obtained by comparing Slope-Hunter’s assignments of the SNPs to the G 1 class with their true class status.…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate Slope-Hunter’s estimations of the G 1 class membership probabilities, we calculated the mean probability for the SNPs identified as the G 1 class. Moreover, the misclassification error rate [18, 19] was obtained by comparing Slope-Hunter’s assignments of the SNPs to the G 1 class with their true class status.…”
Section: Methodsmentioning
confidence: 99%
“…By this evaluation, one could check the ability of genes that regulate the tissue target class. Authors have used different gene selection methods and have shown that gene selection methods have significant effect on a classifier accuracy 25,26 . The same approach has been utilized in another study 14 .…”
Section: P R O V I S I O N a L L Y A C C E P T E D F O R P U B L I C A T I O Nmentioning
confidence: 99%